2018
DOI: 10.1002/smll.201703990
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Direct H2O2 Generation Catalysis by Using Hollow Pd–Sn Intermetallic Nanoparticles

Abstract: Although direct hydrogen (H ) oxidation to hydrogen peroxide (H O ) is considered as a promising strategy for direct H O synthesis, the desirable conversion efficiency remains formidable challenge. Herein, highly active and selective direct H oxidation to H O is achieved by using hollow Pd-Sn intermetallic nanoparticles (NPs) as the catalysts. By tuning the catalytic solvents and catalyst supports, the efficiency of direct H oxidation to H O can be optimized well with the hollow Pd Sn NPs/P25 exhibiting H O se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 39 publications
5
35
0
Order By: Relevance
“…We have recently reported that it is possible to significantly enhance the selectivity of Pd-based catalysts towards H2O2 through the encapsulation of small Pd nanoparticles in a suitable secondary metal oxide, removing the requirement of Au incorporation to achieve a highly selective Pd catalyst in the absence of acid or halide stabilizing agents [23]. With subsequent studies further demonstrating the remarkable effects of Pd modification by Sn [24,25]. While others have investigated the beneficial effects of Zn [26], Ni [27], and Te [28] into Pd nanoparticles, with computational studies by Xu et al predicting Pd-Pd and Pd-W as potential candidates for highly active catalysts for the direct synthesis of H2O2 [29].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that it is possible to significantly enhance the selectivity of Pd-based catalysts towards H2O2 through the encapsulation of small Pd nanoparticles in a suitable secondary metal oxide, removing the requirement of Au incorporation to achieve a highly selective Pd catalyst in the absence of acid or halide stabilizing agents [23]. With subsequent studies further demonstrating the remarkable effects of Pd modification by Sn [24,25]. While others have investigated the beneficial effects of Zn [26], Ni [27], and Te [28] into Pd nanoparticles, with computational studies by Xu et al predicting Pd-Pd and Pd-W as potential candidates for highly active catalysts for the direct synthesis of H2O2 [29].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years focus has shifted towards alloying Pd with a range of non-precious metals, with numerous studies reporting the enhanced catalytic efficacy achieved through the introduction of Sn [35,36], Ag [37], Zn [38], Ni [39,40], In [41,42], Sb [43], and Te [44] into Pd nanoparticles. Typically, the improved selectivity of the bimetallic catalysts has been attributed to a combination of a reduction of contiguous Pd ensembles and a modification of Pd oxidation state.…”
Section: Resultsmentioning
confidence: 99%
“…This idea‐derived new system delivered a significantly high H 2 O 2 selectivity (>90%) as well as a H 2 O 2 productivity of 3660 mol H2O2 kg cat –1 h –1 , which are superior to those provided in a number of previous reports ( Table 4 , Figure 19c,d). [ 12,41,42,76,140,153–161 ] . The completed system also retained nearly 100% of its activity over 100 h of reaction even in high or low concentration of H 2 O 2 (Figures 19e,f).…”
Section: Other Advanced Catalytic Systems For Direct H2o2 Synthesismentioning
confidence: 99%